Monstrous Motherhood and Repetitive Trauma in Lucy Rose’s The Lamb - Rasya Putri Ramadina; Ice Sariyati; Hasbi Assiddiqi (Journal of English Language and Education, 2026)
Contemporary Female Gothic situates horror within the domestic sphere, often centering the maternal figure as a source of threat. This study examines monstrous motherhood and repetitive trauma in The Lamb by Lucy Rose, focusing on how the mother–child relationship normalizes and reproduces domestic violence. While previous studies have discussed monstrous motherhood and trauma in Gothic narratives, limited attention has been given to their interconnected role within everyday maternal relationships. Employing a qualitative interpretive approach, this study applies close reading and thematic coding to selected narrative passages. The analysis draws on Female Gothic criticism, Barbara Creed’s concept of monstrous motherhood, and Cathy Caruth’s trauma theory. The findings show that violence is normalized through domestic care and repeated across relationships, positioning trauma as a continuous relational structure rather than an individual experience.